Influential Factors Affecting Earnings Management in Public Listed Companies: A Conceptual Model - Algrady, Sayaf; Xiaojun, Xie (International Review of Management and Marketing, 2022)
The issue of earnings management in public listed companies has gained an increasing attention from academicians and policy makers due to its impact on stakeholders’ decision-making. Researchers found that the main factors influencing earnings management can be grouped under internal and external corporate governance aspects. This study proposed a comprehensive model combining some internal and external corporate governance factors affecting earnings management. Based on a review and synthesis of relevant literature, the current study concludes that audit committee characteristics, auditor reputation and audit opinion have a significant impact on earnings management. Further, we predict that auditor reputation has a potential mediating role on the relationship between audit committee characteristics and earnings management, and on the relationship between audit committee characteristics and audit opinion. This research extends the scholarship on earnings management literature and has the potential to provide a set of recommendations to investors and regulatory entities.